Research on deterministic networking requirements and technologies for RDMA-WAN - Junfeng ZHAO; Fang LI; Xiaofeng YE; Song JIANG (Dianxin kexue)
With the rapid development of AIGC large models and intelligent computing applications, deterministic networking technology for wide-area RDMA has become a recent research hotspot.The development path, implementation solutions and technical challenges of RDMA-WAN were analyzed, by setting up a laboratory and an outfield testing environment, with a series of testing and verifications.The deterministic demand characteristics and boundary performance indicators of RDMA-WAN were proposed.Finally, the deterministic networking technologies for RDMA-WAN were summarized and prospected.